2001
DOI: 10.1002/jcc.1117
|View full text |Cite
|
Sign up to set email alerts
|

NMR 3J(C1,H3) couplings in 1‐X‐bicyclo[1.1.1]pentanes. FPT–DFT and NBO studies of hyperconjugative interactions and heavy atom substituent effects

Abstract: ABSTRACT:In this work a rationalization of the very large substituent effects on 3 J(C 1 ,H 3 ) couplings in 1-X-bicyclo[1.1.1]pentanes is presented. The Fermi contact contribution to such couplings was calculated in a series of 13 X-derivatives within the DFT-B3LYP framework using the finite perturbation theory. Core electrons for atoms beyond the Second Row were taken into account using effective core potentials. Calculated couplings are in very good agreement with experimental values. The role played by hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…It is observed that compounds of series (2) transmit these longrange 'trans-cage' SSCCs notably more efficiently than the analogous member of series (1) transmits the corresponding Table 1. Comparison between experimental 1 J C 3 H 3 in (1) and 1 H / 13 C 1 J C 3 C Me SSCCs in (2) (in Hz) and substituent effects 3 J C 1 H 3 X / 3 J C 1 H 3 H in (1) and 3 Table 1, substituent effects are smaller in (2) than in (1). This is equivalent to saying that SSCCs in (2) are basically more efficiently transmitted than in (1), but such transmissions in (2) are notably less affected by substituent effects than in ( 1).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…It is observed that compounds of series (2) transmit these longrange 'trans-cage' SSCCs notably more efficiently than the analogous member of series (1) transmits the corresponding Table 1. Comparison between experimental 1 J C 3 H 3 in (1) and 1 H / 13 C 1 J C 3 C Me SSCCs in (2) (in Hz) and substituent effects 3 J C 1 H 3 X / 3 J C 1 H 3 H in (1) and 3 Table 1, substituent effects are smaller in (2) than in (1). This is equivalent to saying that SSCCs in (2) are basically more efficiently transmitted than in (1), but such transmissions in (2) are notably less affected by substituent effects than in ( 1).…”
Section: Resultsmentioning
confidence: 94%
“…This role can be identified with the role played by delocalization interactions in transmitting the spin information associated with the FC interaction corresponding to long-range SSCCs in saturated compounds. In this way, it is expected that any hyperconjugative interaction along the coupling pathway (Scheme 2) should increase the efficiency for transmitting, for instance, 3 J C 1 H 3 in (1) and 3 J C 1 C Me in ( 2). Of course, there are three similar coupling pathways for each compound.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations